Infections due to Candida spp in a Brazilian Tertiary Hospital: Species and Susceptibility to Antifungals - de Carvalho, Rafaela Durrer Parolina; Pavanello, Larissa; dos Santos, Victor Augusto Benedicto; de Almeida, Talita Bonato; da Silva, Diego Romário; Rosa, Caroline Sanches; Rosa, Fernanda Silveira; de Moraes, Hamilton Antonio Bonilha; Cogo-Müller, Karina (ARCHIVES OF HEALTH INVESTIGATION, 2022)
Introduction: Infections caused by Candida spp are a major public health concern, due to the high mortality rate and the limited therapeutic arsenal. Objectives: To assess the prevalence of Candida spp infections and susceptibility to antifungal agents in a general hospital. Methods: Descriptive, cross-sectional study with collection of epidemiological and laboratory data on Candida spp cultures (2014 to 2019), at a large tertiary and philanthropic hospital in the city of Piracicaba, São Paulo state, Brazil. Results: A total of 63 episodes of Candida spp infection were eligible, being more prevalent in adults (88.9%) aged ≥ 70 years (41.3%), causing 40 deaths (63.5%). The C. albicans species represented 41.3% of the infections, with a mortality rate of 37.5%, while non-albicans species accounted for 58.7%, highlighting C. tropicalis (25.4%) and C. glabrata (23.8%), with a mortality rate of 27.5% for both species. Regarding the susceptibility profile, most were sensitive to echinocandins and azoles over the years. C. glabrata presented one case of resistance and dose-dependent sensitivity to caspofungin and micafungin and fluconazole, which was expected due to the decreased sensitivity to azoles, while the results for echinocandins were in agreement with previous studies showing increased resistance to this group of drugs. Conclusion: Given the high prevalence of hospital fungal infections and the associated mortality rate, determining the local epidemiological profile and susceptibility to drugs is an important strategy for guiding antifungal therapy.